2016
DOI: 10.1021/acs.jafc.5b05180
|View full text |Cite
|
Sign up to set email alerts
|

Structure Characterization and Immunomodulating Effects of Polysaccharides Isolated from Dendrobium officinale

Abstract: A crude polysaccharide fraction (cDOP) has been determined to be the characteristic marker of Dendrobium officinale, an expensive tea material in Asia, but its chemistry and bioactivity have not been studied. In work reported here, cDOP was destarched (DOP, 90% yield) and separated into two subfraction polysaccharides, DOPa and DOPb, which were characterized by monosaccharide composition and methylation analyses and spectral analyses (FT-IR and (1)H and (13)C NMR). Both are composed of mannose and glucose at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(41 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…Activation of macrophages can enhance their antitumor activity through secretion of cytokines or regulation of the immune system [ 29 ]; thereby, it is commonly assessed to examine the immunomodulatory function of polysaccharides [ 21 , 30 ]. In this study, macrophage immunological activity assay revealed that RS-3-1, BZ-3-1, FL-3-1, and GC-3-1 could enhance phagocytosis, promote NO production, and increase tumor necrosis factor (TNF- α ) level in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of macrophages can enhance their antitumor activity through secretion of cytokines or regulation of the immune system [ 29 ]; thereby, it is commonly assessed to examine the immunomodulatory function of polysaccharides [ 21 , 30 ]. In this study, macrophage immunological activity assay revealed that RS-3-1, BZ-3-1, FL-3-1, and GC-3-1 could enhance phagocytosis, promote NO production, and increase tumor necrosis factor (TNF- α ) level in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…RAW264.7 cells (1 × 10 4 cells/well) were seeded in 24-well plates and incubated overnight. Serial dilutions of polysaccharide samples (1, 10, 50, 100, and 500 μ g/mL), DMEM medium and LPS (5 μ g/mL) were then added, and the cells were incubated for another 24 h. The supernatants were collected and analyzed using an ELISA kit according to the manufacturer's instructions to determine the level of TNF- α secretion [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…CellTiter 96 ® AQueous One Solution Cell Proliferation kit was purchased from Promega Inc. (Madison, WI, USA). Polysaccharide marker DOP of Dendrobium officinale was prepared in our previous study [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, a unique polysaccharide marker (glucomannan, called DOP) was identified for the authentication of D. officinale [ 13 ]. DOP is likely also to be the main active ingredient because its content exceeds 30% of the dry herb by weight, and it shows immunomodulating effects towards immune cells [ 14 , 15 , 16 , 17 ]. Therefore, we hypothesize that DOP also has anti-fatigue activity.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrobium officinale (Chinese name: Tie-pi-shi-hu ) is an edible perennial orchid plant that has commonly been employed as a functional food in China and other Asian countries for thousands of years [ 1 ]. D. officinale is frequently infused in juice, tea and wine as a functional liquid, but can also be chewed directly or stewed in soup, porridge and other dishes as a high-quality agricultural vegetable in dietary supplementation [ 2 ], and has been approved by the China Food and Drug Administration ( ). Phytochemical analyses of stems in D. officinale have validated the presence of antioxidants [ 3 ], which are associated with anti-angiogenesis [ 4 ], immuno-stimulating activity [ 5 ] and the attenuation of ulcerative colitis [ 6 ], biofunctional properties that are due to large amounts of polysaccharides, flavonoid, phenanthrenes, bibenzyls and polyphenolic compounds [ 7 ].…”
Section: Introductionmentioning
confidence: 99%